2021
DOI: 10.3389/fmolb.2021.692668
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Methyltransferases as Regulators of RNA-Binding Protein Activities in Pathogenic Kinetoplastids

Abstract: A large number of eukaryotic proteins are processed by single or combinatorial post-translational covalent modifications that may alter their activity, interactions and fate. The set of modifications of each protein may be considered a “regulatory code”. Among the PTMs, arginine methylation, catalyzed by protein arginine methyltransferases (PRMTs), can affect how a protein interacts with other macromolecules such as nucleic acids or other proteins. In fact, many RNA-binding (RBPs) proteins are targets of PRMTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…and Chagas disease ( T. cruzi ) belong to the kinetoplastids group (trypanosomatids). The main mechanisms implicated in the regulation of gene expression in these parasites are the post-transcriptional processes, including RNA turnover, translation and editing, involving multiple RNA-binding proteins (RBPs), which are common targets of arginine methylation (Campagnaro et al ., 2021). These microorganisms contain five PRMTs, which are homologues to the mammalian PRMT1, 3, 5, 6 and 7 (Fisk and Read, 2011); the studies related to these enzymes have been performed on the five enzymes of T. brucei and on the PRMT7 of Leishmania major , whereas there are no reports about the role of PRMTs in other Leishmania species or in T. cruzi .…”
Section: Arginine Methylation and Prmts In Protozoan Parasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…and Chagas disease ( T. cruzi ) belong to the kinetoplastids group (trypanosomatids). The main mechanisms implicated in the regulation of gene expression in these parasites are the post-transcriptional processes, including RNA turnover, translation and editing, involving multiple RNA-binding proteins (RBPs), which are common targets of arginine methylation (Campagnaro et al ., 2021). These microorganisms contain five PRMTs, which are homologues to the mammalian PRMT1, 3, 5, 6 and 7 (Fisk and Read, 2011); the studies related to these enzymes have been performed on the five enzymes of T. brucei and on the PRMT7 of Leishmania major , whereas there are no reports about the role of PRMTs in other Leishmania species or in T. cruzi .…”
Section: Arginine Methylation and Prmts In Protozoan Parasitesmentioning
confidence: 99%
“…Leshmania sp. has five PRMT homologues to those of T. brucei , but studies showed certain differences, for example, the L. major PRMT3 has an intact double E loop, suggesting that it could be an active enzyme (Campagnaro et al ., 2021). The expression of LmPRMT7 is high in the promastigote logarithmic growth phase and intracellular amastigotes, but low in the promastigote stationary phase (Ferreira et al ., 2014).…”
Section: Arginine Methylation and Prmts In Protozoan Parasitesmentioning
confidence: 99%
“…RBPs are dynamically regulated by post-translational modifications (PTM) [15][16][17] . For example, the highly conserved and abundant arginine-glycine (RG)-rich domains in RBPs can be methylated 18,19 . Arginine methylation is catalyzed by arginine methyltransferases (RMTs), which are similarly diverse across the evolutionary landscape 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these are the only protozoan parasites known thus far to harbor type I, II, and III PRMTs, which suggests that arginine methylation may play a critical role during the life cycles of these protozoa. 12,13 In addition to their medical relevance, trypanosomatids are unique eukaryotes because of their particular genetic organization that regulates gene expression, and this regulation of gene expression is mostly dependent on posttranscriptional regulatory mechanisms. 14−17 Within the past two decades, thorough investigations of PRMTs and arginine methylation have been conducted in Trypanosoma brucei.…”
mentioning
confidence: 99%
“…and Leishmania spp., are early branching, medically relevant protozoa that carry five different classic PRMT genes (PRMT1, PRMT3, PRMT5, PRMT6, and PRMT7). In fact, these are the only protozoan parasites known thus far to harbor type I, II, and III PRMTs, which suggests that arginine methylation may play a critical role during the life cycles of these protozoa. , …”
mentioning
confidence: 99%